2018
DOI: 10.1097/aud.0000000000000673
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Effects in Children’s Ability to Benefit From F0 Differences Between Target and Masker Speech

Abstract: Objectives: The objectives of this study were to (1) evaluate the extent to which school-age children benefit from fundamental frequency (F0) differences between target words and competing two-talker speech, and (2) assess whether this benefit changes with age. It was predicted that while children would be more susceptible to speech-in-speech masking compared to adults, they would benefit from differences in F0 between target and masker speech. A second experiment was conducted to evaluate the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
48
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 70 publications
16
48
7
Order By: Relevance
“…Adults' VTL JNDs did not significantly differ from those of 8-to 12-year-old children, whereas adults' F0 JNDs differed from children's F0 JNDs at all ages. The increase in sensitivity to differences in F0 cues with age is in line with previously reported research [10][11][12][13] . The differences in the reported ages at which children's discrimination of F0 is adult-like are likely due to differences in stimuli and task demands.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Adults' VTL JNDs did not significantly differ from those of 8-to 12-year-old children, whereas adults' F0 JNDs differed from children's F0 JNDs at all ages. The increase in sensitivity to differences in F0 cues with age is in line with previously reported research [10][11][12][13] . The differences in the reported ages at which children's discrimination of F0 is adult-like are likely due to differences in stimuli and task demands.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we investigated whether children's ability to discriminate voice gender cues (Experiment 1) and how they weigh voice gender cues for categorization (Experiment 2) develop similarly for F0 as for VTL cues, the primary cues of voice gender, and at what age children's performance is adult-like. Previous studies have shown that children's discrimination of F0 continues to develop throughout childhood, but some of these studies measured pure-tone frequency discrimination using non-voice stimuli 11,40 instead of discrimination of more realistic voice pitch cues using voice stimuli 12,13 . Regarding VTL, discrimination has only been studied before in infants and only using EEG, which, while providing some evidence of processing of the acoustic traits associated with VTL, does not necessarily reflect perception 5 .…”
mentioning
confidence: 99%
“…Speech produced by males and females generally differs across multiple acoustic features, including F0, dispersion of formant frequencies, and phonation type (e.g., Fitch and Giedd, 1999). In a later study, Flaherty et al (2019) observed a striking age effect in the ability to benefit from target/masker differences only in F0, holding other acoustic target/masker differences constant. Whereas adults and older children (>13 years) showed a robust benefit associated with target/masker differences in mean F0, younger children (<7 years) did not.…”
Section: Factors Responsible For Developmental Effectsmentioning
confidence: 80%
“…Whereas adults and older children (>13 years) showed a robust benefit associated with target/masker differences in mean F0, younger children (<7 years) did not. Flaherty et al (2019) suggested that children might require additional acoustic cues (e.g., distribution of formant frequencies) in order to perceptually isolate target and masker speech. Additional evidence supporting this interpretation is provided by normative data for the LiSN-S clinical test (e.g., Cameron et al, 2009, 2011; Brown et al, 2010).…”
Section: Factors Responsible For Developmental Effectsmentioning
confidence: 99%
“…Children may be at a disadvantage under challenging listening conditions due to the increased importance of high-rate cues, the very cues that they are less adept than adults at using. For example, a recent study by Flaherty et al (2018) reported that whereas adults benefit from an F0 difference between the target and masker speech, young children derive little or no benefit from F0 mismatches. One possible factor contributing to this result is that children's limited temporal resolution for high-rate envelope cues interferes with their ability to utilize segregation cues based on differences in voice F0.…”
Section: Discussionmentioning
confidence: 99%